PENGARUH DER, PDB DAN EPS TERHADAP HARGA SAHAM PERUSAHAAN ASURANSI YANG TERDAFTAR DI BEI - Putri Aulia Febrianti; Nurhayati Nurhayati (Media Ekonomi, 2019)
This research purpose is to discover the influence of Debt Equity Ratio (DER), Gross Domestic Product (GDP), and Earning Per Share (EPS) to The Price of stocks of insurance company which are listed in Indonesia Exchange Stock. The  research  method  used  in  this  study  is  quantitative  research  methods.  The  sample  is  5  insurance companies listed in Indonesia Exchange Stock  which  were  previously   determined   by   the   purposive sampling   method.   Data  collected  in  the  form  of  annually financial  reports  for  each  Insurance companies listed in Indonesia Exchange Stock from  2014 -2018  The  analysis  technique  used  is  panel  data  regression. Based on the analysis conducted stated that DER has a negative effect on the stock prices of insurance companies and GDP, EPS has a positive influence on the stock prices of insurance companies listed on the Indonesian Exchange Sctock. However, on the other hand the growth of gross domestic product has a direct and significant effect on the value of shares of insurance companies listed on the Indonesian Exchange Stock.